2013
DOI: 10.1021/ef400774b
|View full text |Cite
|
Sign up to set email alerts
|

Fly Ash Deposition during Oxy-fuel Combustion in a Bench-Scale Fluidized-Bed Combustor

Abstract: Ash deposition on heat-exchanger surfaces in boiler systems can cause numerous problems, including slagging, fouling, and corrosion. These deleterious processes can be compounded if the boiler combustion process is changed from air to oxy-fuel. In this paper, fly ash deposition characteristics under both air and oxy-fuel combustion conditions were investigated using a bench-scale fluidized-bed combustor (FBC) based on measurements of ash deposition rates via a temperature-controlled probe. Three different comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 21 publications
1
18
2
Order By: Relevance
“…Ash deposition on heat exchanger surfaces of boiler systems might cause several problems, such as slagging, fouling and/or corrosion. For that reason, Zheng et al at the Harbin Institute of Technology (China) studied the fly ash deposition characteristics under both air and oxy‐fuel combustion conditions in a bench scale FBC unit. This study demonstrated a greater tendency for fly ash deposition during oxy‐FB combustion than for air‐firing atmosphere.…”
Section: Oxy Combustion In Fluidized Bedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ash deposition on heat exchanger surfaces of boiler systems might cause several problems, such as slagging, fouling and/or corrosion. For that reason, Zheng et al at the Harbin Institute of Technology (China) studied the fly ash deposition characteristics under both air and oxy‐fuel combustion conditions in a bench scale FBC unit. This study demonstrated a greater tendency for fly ash deposition during oxy‐FB combustion than for air‐firing atmosphere.…”
Section: Oxy Combustion In Fluidized Bedsmentioning
confidence: 99%
“…Zheng et al conducted ash deposition experiments in a bench scale FBC under both oxy‐fuel and air combustion conditions. The results showed a higher tendency for fly ash deposition during oxy‐CFB combustion than for air‐firing mode.…”
Section: Design and Operational Issuesmentioning
confidence: 99%
“…The Harbin Institute of Technology (HIT) research group has conducted several tests on ash deposition under oxyfuel combustion conditions on a bench-scale fluidized-bed reactor. When an anthracite was considered, the ash deposition rate increased in the order of 21% O 2 /79% CO 2 < air <30% O 2 /70% CO 2 . The significantly higher deposition rate in 30% O 2 /70% CO 2 was attributed to the higher production of PM 10 and coarser particle size of the fly ash, compared with the other two combustion cases.…”
Section: Ash Formation and Deposition In Oxy-fbcmentioning
confidence: 94%
“…The details about controlling probe surface temperature can be found in Refs. and . The temperature controlling system is the same as that of the previous ash deposit probe.…”
Section: Experiments and Methodsmentioning
confidence: 99%